2018
DOI: 10.3389/fimmu.2018.03026
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Glycolysis and ATP Production Attenuates IL-33-Mediated Mast Cell Function and Peritonitis

Abstract: Cellular metabolism and energy sensing pathways are closely linked to inflammation, but there is little understanding of how these pathways affect mast cell function. Mast cells are major effectors of allergy and asthma, and can be activated by the alarmin IL-33, which is linked to allergic disease. Therefore, we investigated the metabolic requirements for IL-33-induced mast cell function, to identify targets for controlling inflammation. We found that IL-33 increases glycolysis, glycolytic protein expression,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 63 publications
2
45
1
Order By: Relevance
“…Alternatively, the reduced glycolytic rate may prevent the production of carbon intermediates required for cytokine production, through limiting the repurposing of TCA cycle enzymes (Menk et al, 2018;Williams, O'Neill, & O'Neill, 2018). This would result in a negative feedback loop reducing the inflammatory response (Caslin et al, 2018;McGettrick & O'Neill, 2013). It has been reported that in macrophages 2-DG reduces mitochondrial function independently of glycolytic function (Wang et al, 2018); however, in our data there was no change in oxidative rate as a result of 2-DG treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…Alternatively, the reduced glycolytic rate may prevent the production of carbon intermediates required for cytokine production, through limiting the repurposing of TCA cycle enzymes (Menk et al, 2018;Williams, O'Neill, & O'Neill, 2018). This would result in a negative feedback loop reducing the inflammatory response (Caslin et al, 2018;McGettrick & O'Neill, 2013). It has been reported that in macrophages 2-DG reduces mitochondrial function independently of glycolytic function (Wang et al, 2018); however, in our data there was no change in oxidative rate as a result of 2-DG treatment.…”
Section: Discussioncontrasting
confidence: 59%
“…These molecules augment the ability of IL‐33 Tregs to inhibit Teff responses through the production of adenosine from ATP. Extracellular ATP can act as a danger signal in response to cell damage, 63 with reports suggesting that IL‐33 and ATP may act to induce the release of one another under inflammatory conditions 64,65 . Thus coupled with reports that there is substantial release of IL‐33, ATP, and other alarmin/DAMPS after transplantation, IL‐33 Tregs may have a unique potential in modulating inflammation within an allograft microenvironment 66‐68 .…”
Section: Discussionmentioning
confidence: 97%
“…7A, 7B). In a previous manuscript, we showed that micromolar quantities of labeled ATP diffuse into BMMC within 20 min (51), which can increase the ATP available in the cell for energy and bypass the need for ATP produced by glycolysis. These data, together with the experiments above, suggest that lactic acid suppresses LPS-induced glycolytic ATP production, effectively attenuating energy available for cell signaling and cytokine production (Fig.…”
Section: Atp Reverses Lactic Acid Suppressionmentioning
confidence: 89%